OAGB Bowel Function in Patients With up to 5 Years Follow-Up: Updated Outcomes - Rossoni, C (2023)
Objective: One-anastomosis gastric bypass (OAGB) is considered an effective technique in weight reduction and remission of comorbidities. However, in common with many bariatric and metabolic/bariatric procedures, gastrointestinal side effects are frequently reported, but clinical experience varies. The objective of this study was to analyze the bowel function of patients who undergo OAGB looking at 5-year postoperative outcomes. Method: This study is cross-sectional, descriptive and analytical, developed with individuals undergoing OAGB (n = 208) in yhe period between 2015 and 2020. The time periods evaluated were 1 to 6 months (T1), 6 to 12 months (T2), and 1 to 5 years (T3). Data analysis was performed using SPSS v.28.0, considering a significance level p ≤ 0.05. Results: 114 participants (54.8%), 79.8% women, mean age 47.0 ± 12.6 years, and BMI 40.1 ± 5.6 kg/m2, 51.9% dyslipidemia, 43.6% arterial hypertension, and 19.1% diabetes mellitus. The T1 group had more severe symptoms/nausea than the T2 group. The T2 group had a significantly lower defecation frequency than the T1 and T3 groups. As for the occurrence of diarrhea, associations were not found in the considered groups. The T3 group had a greater severity of constipation associated with greater difficulty in consuming red meat, white meat, rice, vegetables, and salads. Conclusions: Gastrointestinal symptoms are prevalent in the first postoperative months. However, diarrhea was not common. The patient selection policy and surgical technique were decisive in this result. Constipation was prevalent in patients between 1 and 5 postoperative years. It was also prevalent in those who had food intolerance, which from a nutritional point of view is an adverse factor for optimal bowel function.